Knowledge Management Design Using Collaborative Knowledge Retrieval Function - Suryadi, Kadarsah; Sigit Pramudyo, Cahyono (School of Business and Management Institut Teknologi Bandung, 2008)
Knowledge is a key word in the information age. Organizational knowledge provides businesses with a way to compete effectively and efficiently in the market. The performance of many organizations is determined more by their knowledge than their physical assets. Capturing and representing knowledge is critical in knowledge management. The spread of organizational knowledge has made a difficulty in sharing knowledge. This problem creates a longer learning cycle. This research proposes a web based knowledge map, using collaborative knowledge retrieval function, as a tool to represent and share knowledge. First, knowledge map gives a comprehensive understanding about what knowledge is needed to achieve objectives, what knowledge sources are available, and which knowledge sources are used by whom. Second, web facilitates knowledge sharing. Third, collaborative knowledge retrieval function will shorten learning cycle. Fourth, the proposed tool is applied to build a web based knowledge for an academic system in higher education. The result of this research is a design of web based knowledge map using collaborative knowledge retrieval function. Collaborative retrieval knowledge function gives recommendations of relevant knowledge between web documents. The proposed model contributes in shortening the learning cycle.Keywords: Knowledge map, Collaborative retrieval knowledge function, Web, Learning cycle, Knowledge Sharing.